2017
DOI: 10.1093/eurpub/ckx212
|View full text |Cite
|
Sign up to set email alerts
|

The role of financial strain and self-control in explaining health behaviours: the GLOBE study

Abstract: BackgroundWhy lower socioeconomic groups behave less healthily can only partly be explained by direct costs of behaving healthily. We hypothesize that low income increases the risk of facing financial strain. Experiencing financial strain takes up cognitive ‘bandwidth’ and leads to less self-control, and subsequently results in more unhealthy behaviour. We therefore aim to investigate (i) whether a low income increases the likelihood of experiencing financial strain and of unhealthy behaviours, (ii) to what ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 32 publications
5
50
1
Order By: Relevance
“…Likewise, a cross‐sectional study found that financial strain, as measured by questions asking to what extent participants could make ends meet and experienced financial difficulties in paying bills for basic needs (e.g. food, electricity) in the preceding year, was associated with decreased fruit and vegetable intake (Beenackers et al., ). Also, a longitudinal study showed that evaluations of the family as very poor to just getting by given needs and financial responsibilities increased calorie but decreased fruit and vegetable consumption (Venn & Strazdins, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a cross‐sectional study found that financial strain, as measured by questions asking to what extent participants could make ends meet and experienced financial difficulties in paying bills for basic needs (e.g. food, electricity) in the preceding year, was associated with decreased fruit and vegetable intake (Beenackers et al., ). Also, a longitudinal study showed that evaluations of the family as very poor to just getting by given needs and financial responsibilities increased calorie but decreased fruit and vegetable consumption (Venn & Strazdins, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the adverse impact of scarcity on eating behaviour as an explanation for unhealthy diets among people with low income has been suggested before (Mullainathan & Shafir, ; Spears, ), empirical evidence remains scarce. A recent cross‐sectional study showed that financial scarcity (financial strain) indeed related negatively to self‐reported health behaviours including fruit and vegetable intake (Beenackers, Oude Groeniger, van Lenthe, & Kamphuis, ), whereas a longitudinal study found that financial strain had limited to no effect on diet‐related health outcomes including being overweight (Prentice, McKillop, & French, ). To our knowledge, Bratanova, Loughnan, Klein, Claassen, and Wood () showed the first experimental evidence for a causal effect of perceptions of poverty on unhealthy eating.…”
Section: Introductionmentioning
confidence: 99%
“…We found only a few studies that considered subjective measures of economic distress, all of which examined alcohol, but not drug abuse as an outcome. [32][33][34] Kalousova and Burgard 34 found perceived decline in economic resources was associated with incidence of alcohol abuse, although unemployment and measured decline in economic resources were not significant. Other studies also found financial strain associated with alcohol abuse, 32 at least in some subgroups.…”
mentioning
confidence: 99%
“…[32][33][34] Kalousova and Burgard 34 found perceived decline in economic resources was associated with incidence of alcohol abuse, although unemployment and measured decline in economic resources were not significant. Other studies also found financial strain associated with alcohol abuse, 32 at least in some subgroups. 33 We hypothesize that: H 2 : Subjective measures of economic distress will be more strongly associated with drug and alcohol abuse than objective measures.…”
mentioning
confidence: 99%
“…Examples of behavioural determinants that have been found relevant and to be targeted in comprehensive interventions are misconceptions and awareness of personal consumption compared to recommendations [26], motivation or attitude [27], self-efficacy [28], taste and liking [29], food label use [30], portion size awareness [31], emotional and mindful eating [32], familiarity towards healthy foods [33,34], perceived convenience of preparation [35], planning [36], and (coping with negative) perceived social norms and lack of social support [28,37]. Environmental barriers for low-SES groups specifically, include the high price of healthy foods [38,39], limited financial resources and financial strain [40][41][42][43][44], and lower accessibility and availability [44]. Educational interventions should target how to deal with these environmental determinants that cannot be changed with nutrition education [20,23,24].…”
Section: Introductionmentioning
confidence: 99%